Assessment of Workers’ Level of Exposure to Work-Related Musculoskeletal Discomfort in Dewatered Cassava Mash Sieving Process - Ahiakwo, A. A.; Simonyan, K. J.; Eke, A. B. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
This study was undertaken to assess the level of exposure of processors to work-related musculoskeletal disorder when using the locally developed traditional sieve in the sieving process. Quick ergonomic checklist (QEC) involving the researcher’s and the processors’ assessment using the risk assessment checklist, was used in this assessment and data was obtained from a sample of one hundred and eight (108) processors randomly selected from three senatorial districts of Rivers State. Thirty-six processors from each zone comprising of 14 males and 22 females, were selected., and assessed on the bases of their back, shoulder/arm, wrist/hand and neck posture and frequency of movement during traditional sieving process. The result of the assessment showed that the highest risk of discomfort occurred at the region of the wrist/hand, followed by back, shoulder/arm, and neck. The posture used in the sieving process exposed the processors, not only to the discomfort of pain but also put them at high risk of musculoskeletal disorder at indicated by a high level of percentage exposure of 66% QEC rating. The result indicated a need for immediate attention and change to an improved method that will reduce the discomfort on the body parts assessed. identified parts.